2016
DOI: 10.1002/chem.201601353
|View full text |Cite
|
Sign up to set email alerts
|

G‐Quadruplex Supramolecular Assemblies in Photochemical Upconversion

Abstract: Parallel, tetramolecular G-quadruplex (G4) DNA possessing TINA monomer, (R)-1-O-[4-(1-pyrenylethynyl)phenylmethyl]glycerol, were synthesised and evaluated in complexes with tris(2,2'-bipyridine)ruthenium(II), [Ru(bpy)3 ](2+) , and the Zn(2+) derivative of 5,10,15,20-tetrakis-(1-methyl-4-pyridyl)-21 H,23H-porphine, ZnTMpyP4. UV/Vis, fluorescence, and circular dichroism (CD) spectroscopy showed that the use of G4-DNA as a template resulted in the effective communication between the ligands and the TINA molecule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Balzani, Ceroni et al.’s alternative mechanistic proposal included an additional step involving triplet–triplet annihilation of pyrene generating pyrene in its singlet‐excited state. Their proposal is based on earlier publications reporting the Ru(bpy) 3 2+ sensitized triplet–triplet annihilation of a pyrene derivative (in supramolecular assemblies), and applications of triplet–triplet annihilated excited singlet species, generated under laser irradiation, for photoredox applications . We would like to emphasize that the same papers (see Refs.…”
Section: Figurementioning
confidence: 92%
“…Balzani, Ceroni et al.’s alternative mechanistic proposal included an additional step involving triplet–triplet annihilation of pyrene generating pyrene in its singlet‐excited state. Their proposal is based on earlier publications reporting the Ru(bpy) 3 2+ sensitized triplet–triplet annihilation of a pyrene derivative (in supramolecular assemblies), and applications of triplet–triplet annihilated excited singlet species, generated under laser irradiation, for photoredox applications . We would like to emphasize that the same papers (see Refs.…”
Section: Figurementioning
confidence: 92%
“…Due to the remarkable ability of TINA-insertions to stabilize NA complexes through intercalation, various TINA-modified oligonucleotides have been further studied as dsDNA targeting fluorescence probes [ 216 , 219 , 220 ], ssDNA targeting fluorescent probes with increased sensitivity and specificity [ 221 ], improved primers for PCR assays [ 222 ], G-quadruplex-forming oligonucleotides [ 223 , 224 , 225 , 226 , 227 , 228 ], i-motif-forming oligonucleotides [ 229 ], aptamers with improved activity [ 230 ], probes for DNA duplex invasion [ 231 ], and antisense oligonucleotides for splice modulation by induced exon-skipping in vitro [ 232 ]. Interestingly, modification of a template oligonucleotide by 5′-terminal o TINA was shown to reduce or even inhibit of a non-templated nucleotide addition activity of DNA polymerases [ 233 ].…”
Section: Agents For Targeting Of Dsdnasmentioning
confidence: 99%
“…[8,9] Recently,a ne xample of this upconversion mechanism has been reported with [Ru(bpy) 3 ] 2+ and ap yrene derivative. [10] Also in the case of pristine pyrene,w eh ave observed that selective excitation of [Ru(bpy) 3 ] 2+ at 532 nm in the presence of 0.01m pyrene in DMSO causes population of Py(S 1 ), as evidenced by the appearance of delayed fluorescence of pyrene,occurring on the mstime scale (see Figure S2 in the Supporting Information).…”
mentioning
confidence: 98%